2022
DOI: 10.1055/a-1765-4035
|View full text |Cite
|
Sign up to set email alerts
|

EUS-guided gastroenterostomy versus surgical gastroenterostomy for the management of gastric outlet obstruction: a systematic review and meta-analysis

Abstract: Background and study aims Surgical gastroenterostomy (SGE) has been the mainstay treatment for gastric outlet obstruction (GOO). The emergence of endoscopic ultrasound-guided gastroenterostomy (EUS-GE) presents a less invasive alternative for palliation of GOO. We conducted a comprehensive review and meta-analysis to compare the effectiveness and safety of EUS-GE compared to SGE. Methods Multiple electronic databases and conference proceedings up to April 2021 were searched to identify studies that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 53 publications
1
9
0
1
Order By: Relevance
“…The most recent systematic review comparing EUS-GE with SGE (seven studies, n = 625 patients) showed lower (pooled odds of) technical success for EUS-GE, albeit with higher per-protocol clinical success, lower overall AEs, and shorter hospital stay. 29 As for comparisons with enteral or duodenal stenting in malignant GOO, three studies have been published to date. 5,25,30 The most recent study by the Leuven-Amsterdam-Milan Study (LAMS)-group compared 176 propensity score-matched patients undergoing either EUS-GE or enteral stenting with uncovered self-expandable metal stents (SEMS).…”
Section: Outcomes and Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent systematic review comparing EUS-GE with SGE (seven studies, n = 625 patients) showed lower (pooled odds of) technical success for EUS-GE, albeit with higher per-protocol clinical success, lower overall AEs, and shorter hospital stay. 29 As for comparisons with enteral or duodenal stenting in malignant GOO, three studies have been published to date. 5,25,30 The most recent study by the Leuven-Amsterdam-Milan Study (LAMS)-group compared 176 propensity score-matched patients undergoing either EUS-GE or enteral stenting with uncovered self-expandable metal stents (SEMS).…”
Section: Outcomes and Indicationsmentioning
confidence: 99%
“…Besides technical aspects of EUS-GE, also more data on comparisons with surgical gastroenterostomy (SGE) and enteral stenting have been emerging (Table 1). The most recent systematic review comparing EUS-GE with SGE (7 studies, n=625 patients), showed lower (pooled odds of) technical success for EUS-GE, albeit with higher per-protocol clinical success, lower overall AE and shorter hospital stay 31 . As for comparisons with enteral or duodenal stenting in malignant GOO, three studies have been published to date 5,27,32 .…”
Section: Outcomes and Indicationsmentioning
confidence: 99%
“…A meta-analysis that compared EUS-GJ with enteral stenting reported comparable success rates and lower rates of reintervention in EUS-GJ (4 vs. 23.6%, P = 0.001) ( 62 ). A meta-analysis that compared EUS-GJ with SGJ showed that EUS-GJ was superior in terms of clinical success, lower overall AE, shorter procedure time, and shorter post-procedure hospital stay ( 63 ). Although there are no officially approved dedicated devices for EUS-GJ in some countries, and the procedure requires experienced hands, it will be necessary to create a treatment decision algorithm that also includes EUS-GJ based on the patient's condition in the future.…”
Section: Considerations For Endoscopic Stentingmentioning
confidence: 99%
“…2 Two independent meta-analyses compared EUS-GJ and surgical GJ for GOO; EUS-GJ exhibited a lower technical success rate than surgical GJ, but similar clinical success and reintervention rates; EUS-GJ was associated with fewer complications. 3,4 Only a few reports of EUS-guided anastomosis (EUS-A) for patients with ALS have appeared. 5 6 and LAMSs in 2015, 7 respectively; efficacy and safety are still under investigation.…”
mentioning
confidence: 99%
“…In a systematic review of 12 studies and 285 cases, the technical success rate was 92% (95% confidence interval [CI] 88–95), while the clinical success rate was 90% (95% CI 85–94), the symptom recurrence rate was 9% (95% CI 6–13), and the adverse event rate was 12% (95% CI 8–16) 2 . Two independent meta‐analyses compared EUS‐GJ and surgical GJ for GOO; EUS‐GJ exhibited a lower technical success rate than surgical GJ, but similar clinical success and reintervention rates; EUS‐GJ was associated with fewer complications 3,4 …”
mentioning
confidence: 99%